Padrão nutricional e alimentar dos integrantes de grupos da melhor idade das cidades de Fortaleza, Itapipoca e Jijoca de Jericoacara - Ceará. - Almendra, Débora Helena Lemos da Fonseca (2007)
The increase of the aged life expectancy and the population of in all the countries and especially in the developing countries, has motivated the interest of on professionals to the health for the people of more advanced age. The group that more grows in the Brazilian population is above of 60 years, represents an important force politics, social and economic, and with this it has called the attention of professionals of diverse areas and also of the government. This work has for objective to delineate the nutritional and alimentary standard of integrant of groups of the best age. The participants of 05 groups of the Best Age (03 groups of the city of Fortaleza, 01 of the city of Itapipoca and 01 of the city of Jijoca de Jericoacora) had been invited both sexs, with rule to chosen teams. Fist became full filled a partner-economic inquiry, an inquiry for evaluation of the health conditions, anthropometric study by the Index of Corporal Mass (ICM) and Relation Waist/Hip, anamnese to feed, for qualitative analysis of the diet of the group of foods of the Alimentary Pyramid. The arterial pressure and the hair glicemia in jejum only of the club of better age of the city of Jijoca de Jericoacoara had been collected. To participate of the second phase, they had been submitted to the mini-mental test to know the cognitive capacity for the auto-register of the recordatório alimentary inquiry 24-hour. An inquiry for evaluation of the nutritional health was carried through. In the total aged searched of both the sex had been 144, 65 had gotten prop up to participate of 2º phase, only 34 had concluded 2ª phase. The biggest band is of 60 the 79 years, the majority of the feminine sex, 72.9% is dedicated to one alone club, majority has incomplete the basic level, 81.9% pensioners, 78.5% develops remunerated activities, wage income of approximately 1-3 minimum wages; 78.3% in habit in proper house; 59.7% to make physical activity, frequency of 2 -3 time per week; 40.3% are sedentary, 18% are carrying of High arterial pressure, 11.5% carriers of constipation and 10.6% carriers of osteoporosis; 12.5% of smokers and 13.2% of alcoholic beverage consumers. The made physical activity without professional accompaniment (65.1%), lack of orientation with regard to nutrition and health (64.6%); 69.4% take medicines, 31% since medicines are of antihypertensives; 67.4% had suffered surgeries; 32.8% of the aged ones only go to the doctor when they are sick, 55.6% to use the public health service. They had been identified high of the glicemia and high cardiac risk; good cognitive level, demonstrating integrity of the brain functions; one proved that the religion does not intervene with the choice of foods; foods rejected for pathology reason had the same had profile of foods rejected for professional orientation, foods that had been rejected by unpleasantness of the palate (rice, chicken and fruits), also had been consumed in the diet. In the evaluation of the alimentary standard, coffee and fruits are consumed foods more in coffee-break, the fruits are consumed mainly in the light meal (snack of the morning); rice and beans in the schedule of the lunch; to the afternoon: coffee and juice with or without complement more are used, the supper are composed of feeding lights or liquid , many aged ones were not fed in the schedule of after the supper. The anthropometric evaluation of the ICM the majority was normal classified. The test of the nutritional health disclosed that it has to change some habits, to consult a doctor or nutritionist, to look the support of the family or to look aid next to programs of assistance for third age.